Sintesis dan Karakterisasi Carbon Nanotube (CNt) dari Arang Kayu Jati serta Pemanfaatannya Sebagai Bahan Aktif Antibakteri - Agung Rimayanto Gintu; Dhanang Puspita (Jurnal Kimia Riset, 2020)
Carbone Nanotube (CNt) was one of antibacterial compound synthesized from carbon pr activated carbon. In this study threated the synthesis of CNt from teak charcoal used strong acid and sonication. The rendement of CNt synthesis showed potential result 37,6555±0,8038%. The characterization to the CNt showed density 1,0145±0,0037g/cc; Absolute Viscosity 1,06±0,0245P.a; Molecule weight 0,0007±0,00002g/mol. Threated the metal ionic doped to the CNt solution used Ag, Cu, Fe(II), Fe(III). Mg and Zn to increase the stabilitation and interaction. The characterization of CNt-Ag showed density 1,0072±0,0055g/cc; Absolute Viscosity 0,66±0,0400P.a; Molecule weight 0,0007±0,00004g/mol. The characterization of CNt-Cu showed density 1,0086±0,0040g/cc; Absolute Viscosity 0,56±0,0400P.a; Molecule weight 0,0007±0,00003g/mol. The characterization of CNt-Fe(II) showed density 1,0060±0,0013g/cc; Absolute Viscosity 0,76±0,0400P.a; Molecule weight 0,0007±0,000001g/mol. The characterization of CNt-Fe(III) showed density 1,0159±0,0042g/cc; Absolyte Viscosity 0,82±0,0200P.a; Molecule weight 0,0007±0,00003g/mol. Characterization of CNt-Mg showed density 0,9970±0,0008g/cc; Absolute Viscosity 0,64±0,0400P.a; Molecule weight 0,0007±0,000005g/mol. Characterization of CNt-Zn showed density 1,0013±0,0013g/cc; Absolute Viscosity 0,60±0,0447P.a; Molecule weight 0,0007±0,000005g/mol. Threated the mix to the CNt by another antibacterial compounds like Hydroxyapatite (HAp), Chitosan and Nano Chitosan. From the characterization of CNt-HAp obtained density 1,0008±0,0010g/cc; Absolute Viscosity 0,60±0,0316P.a; Molecule weight 0,0007±0,000007g/mol. Characterization CNt-Chitosan obtained density 0,9992±0,0019g/cc; Absolute Viscosity 0,42±0,0200P.a; Molecule weight 0,4343±0,0207g/mol. Characterization CNt-Nano Chitosan obtained density 1,0084±0,0002g/cc; Absolute Viscosity 0,50±0,0316P.a; Molecule weight 0,5170±0,3270g/mol. The results of antibacterial activity measurements against E.coli bacteries showed that all of the threatment to the chars produced the antibacterial activity in middle to strong range.